Eficacia de la metodología pilates en las disminución de medidas antropométricas, en personas que presentan sobrepeso - Castillo Pacheco, Katherine Mireya (2017)
OBJECTIVE: To analyze the effect of Pilates exercises on anthropometric measures reduction in people who are overweight. MATERIAL AND METHODS: Ten participants who were overweight, ranging from 19 to 50 years of age, male and female, were randomly assigned to two conditions, one that served as the control group "CG" (5 participants), and the other as the experimental group "EG" (5 participants). Participants of the EG followed a protocol of exercises based on the Pilates method and the participants of the CG did not receive Pilates treatment. RESULTS: At the end of the intervention, the exercise protocol based on the Pilates method significantly modified the BMI (p equal to 0.004) with a reduction of 1.00 kg. The waist circumference showed changes in EG and CG with an average significance of p equal to 0.013 with a reduction of 2 cm. Waist-hip circumference was statistically significant between groups and measurements (p equal to 0.006); However, between pre- and post-treatment (p equal to 0.056) it was not statistically significant in the EG, but a reduction of 0.02 cm. There were statistically significant subcutaneous fold changes: Abdominal p equeal to 0.001 with a reduction of 3.6 mm, supra-iliac p equal to 0.006 with a reduction of 3.8 mm, triceps 0.004 with a reduction of 2.4 mm, medial gastrocnemius p equal to 0.003 with a reduction of 4, 2 mm, subscapular p equal to 0, 0002 with a reduction of 2.6 mm, body fat percentage p equal to 0.008 with a reduction of 2.64 percent. Meanwhile the anterior thigh fold p equal to 0.099 did not show a significant difference between the groups, but it did reduce the measure by 3.8 mm, similarly body fat weight p equal to 0.050 did not show a significant difference but had a considerable reduction of 4.11 kg, after the intervention. CONCLUSIONS: A protocol of exercises based on the Pilates method for a period of 6 weeks, with a frequency of five days a week for 60 minutes, can be effective in reducing BMI, waist circumference, Waist-hip circumference and subcutaneous folds.